If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(s + 22) = 4(s + 2) Reorder the terms: 3(22 + s) = 4(s + 2) (22 * 3 + s * 3) = 4(s + 2) (66 + 3s) = 4(s + 2) Reorder the terms: 66 + 3s = 4(2 + s) 66 + 3s = (2 * 4 + s * 4) 66 + 3s = (8 + 4s) Solving 66 + 3s = 8 + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. 66 + 3s + -4s = 8 + 4s + -4s Combine like terms: 3s + -4s = -1s 66 + -1s = 8 + 4s + -4s Combine like terms: 4s + -4s = 0 66 + -1s = 8 + 0 66 + -1s = 8 Add '-66' to each side of the equation. 66 + -66 + -1s = 8 + -66 Combine like terms: 66 + -66 = 0 0 + -1s = 8 + -66 -1s = 8 + -66 Combine like terms: 8 + -66 = -58 -1s = -58 Divide each side by '-1'. s = 58 Simplifying s = 58
| 3(1-r)+5r=4(r+1)+5 | | 5+x+-3x=3x-2x-1 | | 3.4t+0.008=11 | | -x-30=3x+6 | | 45=3V | | -4r+5=2(2.5-2r) | | M^2+6m-16= | | 14-3(5t+-12)=1-(20t+1) | | 6z-4=9z+14 | | 8x+16=22+8x | | -33=r+(-26) | | (-5)+(9)= | | 14xy-7x^2+5x=0 | | x^2+10x+17=y | | (4x-2y)+70=180 | | 67=13+u | | 25c=675 | | (3m+6n)(7m+2n)= | | X+(x-10)=90 | | -8*+30=10 | | X^2+3x=13 | | x^2+10x+23=y | | 57+4=s | | x^2+34x+c=0 | | 0=(-16t^2)+30t+3 | | 4x-5x+15=-4+3x+3 | | 3(y-1)-7=-2(-8y+3)-7y | | 6k-8k-9k=7 | | 8x+2-10= | | 5x-1+2x+3=12 | | 8n-(6n+7)=5 | | 13+n-20=xy |